Eight weeks of dry dynamic breath-hold training results in larger spleen volume but does not increase haemoglobin concentration - Yang, Kun; Wang, Wen-Bin; Yu, Ze-Hua; Cui, Xiao-Lan; Yu, Zhang-Biao; Jiang, Yi; Gou, Jin-Fei; Du, Meng-Meng (Frontiers in Physiology, 2022)
Purpose: It has previously been reported that repeated exposure to hypoxia increases spleen size and haemoglobin (HGB) level and recent reports on the effect apnoea has on spleen size and haematological parameters are contradictory. Therefore, this study aims to evaluate the effect apnoea training has on spleen size and haematological parameters. Methods: The breath-holding (BH) group was comprised of 12 local student-athletes with no BH exercise experience who performed BH jogging and BH jumping rope dynamic apnoea protocols, five times weekly for eight weeks. The BH event duration was progressively increased as the apnoea tolerance of the athletes improved (20 to 35 s). The same training task was performed by the control group (n = 10) without BH. Spleen sizes were measured with an ultrasound system and a complete blood cell analysis was performed on the median cubital venous blood. Results: Spleen volume in the BH group increased from 109 ±13 mL to 136 ±13 mL (p <0.001),and bulky platelets decreased from 70.50 ±5.83 to 65.17 ±5.87 (p = 0.034), but no changes were recorded for erythrocytes (p = 0.914), HGB (p = 0.637), PLTs (p = 0.346) and WBC (p = 0.532). No changes were recorded for the control group regarding spleen size or haematological parameters. Conclusion: Eight weeks of dry dynamic apnoea training increased spleen size and decreased the number of circulating bulky platelets in the athletes who were assessed in this study. However, the baseline RBC counts and HGB levels of the athletes were not altered by the training programme.